Bio-magnetic nanoparticles based electrochemical biosensor or immunosensor - Ng, Ying Kiat. (2009)
Iron oxide has been long recognized as an important source of chemical compounds for industrial and electronic applications due to the vast range of magnetic properties exhibited by the huge variety of oxides present. Recently, there has been a growing interest in the field of biomedical research to adopt such magnetic particles in nano-size range due to the promising characteristics such as low toxicity, good thermal stability and biocompatibility that they offer.